MANSON'S TROPICAL DISEASES - Cook, Gordon C.; Zumla, Alimuddin I. (Saunders/Elsevier, 2009)
"From the difficult to diagnose to the difficult to treat, be prepared for whatever your patients bring back. The revised and updated 22nd edition of Manson's Tropical Diseases provides you with the latest coverage on emerging and re-emerging diseases from around the world, such as multi-drug-resistant tuberculosis and malaria, the avian flu, and more. Boxes and tables highlight key information on current therapies. And now, as an Expert Consult title, you can access the information you need online as well as in print!"